Diretrizes de conduta e tratamento de síndromes febris periódicas associadas à criopirina (Criopirinopatias–CAPS) - Terreri, Maria Teresa R. A.; Bernardo, Wanderley Marques; Len, Claudio Arnaldo; Silva, Clovis Artur Almeida da; Magalhães, Cristina Medeiros Ribeiro de; Sacchetti, Silvana B.; Ferriani, Virgínia Paes Leme; Piotto, Daniela Gerent Petry; Cavalcanti, André de Souza; Moraes, Ana Júlia Pantoja de; Sztajnbok, Flavio Roberto; Oliveira, Sheila Knupp Feitosa de; et al. (Elsevier B. V., 2015)
To establish guidelines based on cientific evidences for the management of cryopyrin associated periodic syndromes. The Guideline was prepared from 4 clinical questions that were structured through Pico (Patient, Intervention or indicator, Comparison and Outcome), to search in key primary scientific information databases. After defining the potential studies to support the recommendations, these were graduated considering their strength of evidence and grade of recommendation. 1215 articles were retrieved and evaluated by title and abstract; from these, 42 articles were selected to support the recommendations. 1. The diagnosis of Caps is based on clinical history and clinical manifestations, and later confirmed by genetic study. Caps may manifest itself in three phenotypes: FCAS (mild form), MWS (intermediate form) and Cinca (severe form). Neurological, ophthalmic, otorhinolaryngological and radiological assessments may be highly valuable in distinguishing between syndromes; 2. The genetic diagnosis with NLRP3 gene analysis must be conducted in suspected cases of Caps, i.e., individuals presenting before 20 years of age, recurrent episodes of inflammation expressed by a mild fever and urticaria; 3. Laboratory abnormalities include leukocytosis and elevated serum levels of inflammatory proteins; 4. Targeted therapies directed against interleukin-1 lead to rapid remission of symptoms in most patients. However, there are important limitations on the long-term safety. None of the three anti-IL-1β inhibitors prevents progression of bone lesions.

Objetivo: Estabelecer diretrizes baseadas em evidências científicas para manejo das síndromes periódicas associadas à criopirina (criopirinopatias – Caps). Descrição do método de coleta de evidência: A diretriz foi elaborada a partir de quatro questões clínicas que foram estruturadas por meio do PICO (Paciente, Intervenção ou Indicador, Comparação e Outcome), com busca nas principais bases primárias de informação científica. Após definir os estudos potenciais para sustento das recomendações, esses foram graduados pela força da evidência e pelo grau de recomendação. Resultado: Foram recuperados, e avaliados pelo título e resumo, 1.215 artigos e selecionados 42 trabalhos para sustentar as recomendações. Recomendações: 1. O diagnóstico de Caps é baseado na anamnese e nas manifestações clínicas e posteriormente confirmado por estudo genético. Pode se manifestar sob três fenótipos: FCAS (forma leve), MWS (forma intermediária) e Cinca (forma grave). Avaliações neurológica, oftalmológica, otorrinolaringológica e radiológica podem ser de grande valia na distinção entre as síndromes; 2. O diagnóstico genético com análise do gene NLRP3 deve ser conduzido nos casos suspeitos de Caps, isto é, indivíduos que apresentam, antes dos 20 anos, episódios recorrentes de inflamação expressa por urticária e febre moderada; 3. As alterações laboratoriais incluem leucocitose e elevação nos níveis séricos de proteínas inflamatórias; 4. Terapias alvo dirigidas contra a interleucina 1 levam a rápida remissão dos sintomas na maioria dos pacientes. Contudo, existem limitações importantes em relação à segurança em longo prazo. Nenhuma das três medicações anti-IL1 evita progressão das lesões ósseas.
Guidelines for the management and treatment of periodic fever syndromes Cryopyrin-associated periodic syndromes (Cryopyrinopathies-CAPS)
Keywords: Familiar cold autoinflammatory syndrome; Muckle-Wells syndrome; Chronic Infantile Neurologic; Cutaneous and Articular; Syndrome; Autoinflammatory síndromes; Guidelines; Síndrome auto-inflamatória familiar associada ao frio; Síndrome de Muckle-Wells; Síndrome neurológica cutânea e articular crônica infantil; Síndromes auto-inflamatórias; Diretrizes